Analisis Kemampuan Pemecahan Masalah Matematika Berdasarkan Teori APOS Ditinjau dari Tipe Kepribadian David Keirsey - Maulida Yuniarti; Ketut Sarjana; Nilza Humaira Salsabila (Lambda: Jurnal Ilmiah Pendidikan MIPA dan Aplikasinya, 2025)
One of the objectives of mathematics learning is to equip students with problem-solving skills. Each student has different abilities in solving problems, and one of the influencing factors is personality. This study aims to describe students' mathematical problem-solving abilities based on the APOS theory (Action, Process, Object, Schema) in terms of David Keirsey's personality types among eighth-grade students at MTs Negeri 1 Lombok Timur in the 2024/2025 academic year. This research uses a qualitative approach with purposive sampling as the technique for determining research subjects. Data collection was carried out through questionnaires, tests, interviews, and documentation. The results showed that the guardian-type subject was only able to complete 3 out of 4 APOS stages: action, process, and object. The artisan-type subject was only able to complete 2 out of 4 APOS stages: action and process. The rational-type subject was able to complete all APOS stages: action, process, object, and schema. The idealist-type subject was also able to complete all APOS stages: action, process, object, and schema. Thus, it can be concluded that subjects with rational and idealist personality types have better problem-solving abilities than those with guardian and artisan personality types.